2012
DOI: 10.1111/j.1600-0838.2012.01456.x
|View full text |Cite
|
Sign up to set email alerts
|

Exercise for fitness does not decrease the muscular inactivity time during normal daily life

Abstract: Exercise for fitness does not decrease the muscular inactivity time during normal daily life Finni Juutinen, Taija; Haakana, Piia; Pesola, Arto; Pullinen, Teemu Finni Juutinen, T., Haakana, P., Pesola, A., & Pullinen, T. (2014). Exercise for fitness does not decrease the muscular inactivity time during normal daily life. Scandinavian Journal of Medicine and Science in Sports, 24 (1), 211-219. doi:10.1111/j.1600-0838.2012.01456.x The time spent in sedentary behaviors has been shown to be independent of exer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 32 publications
2
27
0
Order By: Relevance
“…Epidemiological studies have implied that in today’s society it is not only possible, but also very common, to exercise regularly yet be highly sedentary during the day (an ‘active couch potato’), and in the present study, there was a rather low association between NEPA and exercise. Finni et al 28 studied how sedentary and NEPA time varied between days with and without intentional exercise by measuring electromyography activity in the quadriceps and hamstring muscle and found that a day including exercise did not significantly alter the time distribution between sedentary pursuits and NEPA, compared to a day without exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have implied that in today’s society it is not only possible, but also very common, to exercise regularly yet be highly sedentary during the day (an ‘active couch potato’), and in the present study, there was a rather low association between NEPA and exercise. Finni et al 28 studied how sedentary and NEPA time varied between days with and without intentional exercise by measuring electromyography activity in the quadriceps and hamstring muscle and found that a day including exercise did not significantly alter the time distribution between sedentary pursuits and NEPA, compared to a day without exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, any activity that decreases inactivity time, like sitting, may benefit health [1][2][3][4][5]13]. …”
Section: Discussionmentioning
confidence: 99%
“…Finni et al [4] have shown that exercise for fitness, regardless of its duration, does not decrease the inactivity time during normal daily life. Further, different counseling interventions have been carried out to decrease sedentary behavior [5].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a recent study in young healthy participants showed that increasing MVPA was not linked to lower sedentary time [29]. Research is also beginning to show that regardless of whether people are meeting public health physical activity recommendations (i.e.…”
Section: Moderate-to-vigorous Physical Activitymentioning
confidence: 99%